Fault protection for a SiC MOSFET based on gate voltage subjected to short circuit type II. (April 2020) - Liao, Xinglin; Shen, Qiping; Hu, Yaogang; Yang, Chao; Chen, Xingang; Li, Hui
Abstract: Given its small chip area and high current density, the fault protection of SiC MOSFET is a serious challenge. In this paper, a gate voltage-based fault protection method for a SiC MOSFET subjected to short circuit type II also called fault under load is proposed. The circuit implementation of the proposed method is analyzed in detail. A test with a voltage of 200 V is conducted. Experimental results verify the effectiveness of the proposed method. It is exhibited the fault response time of the proposed method is less than 1 μs, which is very fast to protect a device and is conducive to the reliable and safe operation of SiC MOSFETs.